The Learning Strategy of Islamic Education at Primary School in Implantation of Islamic Thought Values - Dalmi Iskandar Sultani; Cita Ayni Putri Silalahi; Rahmadi Ali (Universitas Pendidikan Ganesha, 2021)
The implementation of learning strategies that have not been able to make students enthusiastic in participating in learning activities, is due to the lack of application of creative and innovative learning strategies. This study aims to analyze the strategies applied by religious teachers to students, to determine the effectiveness of the strategies involved in cultivating Islamic thought values at Elementary School. This type of research is descriptive research. The subject of this research is to analyze Islamic education strategies. Data collection was carried out by interview, using instruments in the form of interview guides. The data analysis technique in this study uses descriptive qualitative data analysis techniques. The results showed that the strategy of Islamic religious teachers in instilling the values of Islamic thought in students by implementing the K13 curriculum with the talking stick method and snowballing to create effective learning in order to achieve learning objectives by planning making annual programs, semester programs, learning syllabus, lesson plans, and learning evaluation. The implication of this research is to increase students' interest in learning by inviting students to be enthusiastic about learning, creating student creativity, sharing, and having the courage to convey ideas.